Ethanolamine saccharification treatment method for corn straw and application of ethanol amine saccharification treatment method
By treating corn straw with ethanolamine solution and regulating the concentration, temperature and time, the problems of low lignin removal efficiency and low saccharification rate in corn straw pretreatment were solved, and efficient and green straw resource utilization was achieved, which is suitable for bio-based materials and bioethanol fermentation.
Patent Information
- Application Number
- CN202510970279.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-15
- Publication Date
- 2025-10-10
AI Technical Summary
Existing corn straw pretreatment methods have problems such as low lignin removal efficiency, low saccharification rate, complex operation and environmental pollution. There is a lack of systematic research on the influence of ethanolamine treatment conditions and process parameter optimization strategies.
By using ethanolamine solution for pretreatment and regulating parameters such as concentration, temperature and time, the lignin removal effect and sugar yield can be significantly improved under mild conditions. Combined with process optimization and kinetic modeling, a stable and controllable saccharification treatment technology is formed.
High-efficiency lignin removal rate and sugar yield are achieved. The product has high cellulose content and excellent crystallinity. It is suitable for bio-based materials and bioethanol fermentation, and has good industrial promotion prospects and environmental friendliness.
Smart Images

Figure CN120759143A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of crop straw processing and resource utilization, and in particular to a method for ethanolamine saccharification of corn straw, belonging to the technical scope of biomass resource pretreatment, bioconversion and feed or energy preparation. Background Art
[0002] In my country, corn, as one of the main staple crops, ranks among the top in the world in both cultivated area and yield. Consequently, corn straw, with an annual production exceeding hundreds of millions of tons, is a plentiful, low-cost, renewable biomass resource. Rich in cellulose, hemicellulose, and lignin, corn straw offers significant potential for development and utilization. However, due to its dense structure and strong resistance to degradation, untreated corn straw is difficult to use directly as feed, fuel, or chemical raw material. Consequently, large amounts of corn straw are burned or discarded, causing serious environmental pollution and resource waste.
[0003] Currently, corn straw is primarily used as a resource for feed, energy, and materials. Saccharification, which converts straw into reducing sugars and then ferments them into bioethanol, bio-based materials, and other products, is a key path to achieving high-value straw utilization. To improve saccharification efficiency, straw must be pretreated before saccharification to disrupt the lignin structure, expose the cellulose components, and increase their accessibility to enzymes or other saccharifying agents.
[0004] Traditional straw pretreatment methods include physical, chemical and biological methods. Among them, although physical methods (such as crushing, steam explosion, etc.) can improve the reaction efficiency to a certain extent, they have high energy consumption and complex equipment requirements; chemical methods such as dilute acid, concentrated acid or alkaline treatment have good delignification capabilities, but there are problems such as strong corrosiveness, heavy environmental pollution, and many by-products. For example, concentrated acid treatment requires expensive corrosion-resistant equipment and requires post-treatment to remove residual acid; while dilute acid treatment does not completely remove lignin, the sugar yield is low, and it is easy to generate by-products that inhibit fermentation. In addition, the saccharification efficiency of the enzymatic hydrolysis method alone is limited, and the enzyme cost is high and the activity is limited, making it difficult to meet the needs of large-scale applications.
[0005] In recent years, studies have attempted to pretreat straw using organic amine solvents, such as ethanolamine. Ethanolamine molecules possess both amino and hydroxyl functional groups, exhibiting excellent hydrophilicity and alkalinity. They react with phenolic hydroxyl groups in lignin, effectively disrupting the lignin structure and enhancing cellulose exposure. However, existing literature and processes lack systematic research on the effects of ethanolamine treatment conditions on indicators such as lignin removal rate and sugar yield, and lack precise kinetic models and process parameter optimization strategies.
[0006] Therefore, there is an urgent need for a green, efficient, mild and highly controllable corn straw pretreatment saccharification method that can improve the lignin removal efficiency while taking into account the sugar yield and product quality, reduce the environmental burden, and be suitable for actual industrial promotion and application. Summary of the Invention
[0007] To address the challenges of traditional corn straw pretreatment, including low lignin removal efficiency, low saccharification yield, complex operations, and environmental pollution, this paper proposes a pretreatment saccharification method based on an ethanolamine solution. By manipulating parameters such as ethanolamine concentration, reaction temperature, and time, this method significantly improves lignin removal and sugar yield under mild conditions. Combined with process optimization and kinetic modeling, this method creates a stable, controllable, and readily scalable saccharification solution.
[0008] The present invention provides a method and application for the ethanolamine saccharification of corn straw, which is suitable for the efficient saccharification and utilization of straw biomass. The method comprises the following steps:
[0009] (a) pulverizing the collected corn stalks to a particle size within a range of 20-60 meshes to increase the specific surface area and facilitate subsequent reactions;
[0010] (b) mixing the crushed corn stalks with a pre-prepared 10% to 60% aqueous ethanolamine solution at a ratio of 1:10 to 1:25 (g / ml) to ensure good liquid-solid contact in the reaction system;
[0011] (c) performing a reaction treatment at a constant temperature of 30-80° C. for 3-16 hours to achieve sufficient removal of lignin and deconstruction of the cellulose structure;
[0012] (d) After the reaction, solid-liquid separation is performed. The separated solid residue is thoroughly washed with distilled water until the pH is close to neutral, and then dried at 105°C to constant weight. The final product obtained is the saccharification raw material or intermediate. After this treatment, the reducing sugar content in the saccharification liquid can reach 875.09±25mg / g dry straw, and the lignin removal rate is as high as 93.33±2%.
[0013] Furthermore, in order to improve the saccharification efficiency and lignin removal effect, the volume fraction of the ethanolamine aqueous solution in step (b) is preferably controlled to 40±5%, and the mixing ratio of corn straw to solution is selected to be 1:20±2 (g / ml). This ratio can reduce ethanolamine consumption while ensuring the wetting effect.
[0014] Furthermore, the reaction conditions in step (c) preferably satisfy any one of the following groups:
[0015] First, react at a temperature range of 60-80°C for 10±2 hours;
[0016] Secondly, the reaction was carried out at a temperature of 70±2°C for 8-12 hours. Both sets of reaction conditions have obtained good results in the experiment.
[0017] Preferably, in step (d), the solid residue is dried by forced air drying at 105±5°C for 6±0.5 hours until the sample mass no longer changes, thereby ensuring that the obtained saccharification product is fully dried and easy to preserve.
[0018] Preferably, in order to balance delignification ability and economy, the ethanolamine can be selected from any one of monoethanolamine (MEA), diethanolamine (DEA), triethanolamine (TEA) or a combination thereof, and the total molar concentration of ethanolamine in the solution is controlled within the range of 1.5-6.0 mol / L.
[0019] Furthermore, the lignin removal process conforms to a specific kinetic model expression:
[0020] W L =a1exp(-k1t)+a2exp(-k2t)+a3exp(-k3t)
[0021] Among them, W L is the residual mass fraction (%) of lignin at reaction time t (unit: h),
[0022] a1, a2, and a3 are the proportional coefficients of lignin at different stages, satisfying a1+a2+a3=1;
[0023] K1, k2, and k3 are the lignin degradation rate constants corresponding to each stage;
[0024] Preferably, K1 represents the rate constant of the rapid reaction stage (K1=∞), and its value is much larger than k2 and k3. The corresponding stage is completed rapidly at the initial stage of the reaction and can be regarded as instantaneous removal in modeling and fitting.
[0025] The parameters are obtained through regression fitting of experimental data and are used to describe the multi-stage degradation characteristics of lignin.
[0026] In one possible embodiment, the present invention also provides a corn straw saccharification product obtained based on the above method, which has the physical and chemical characteristics of cellulose content ≥74.5wt%, hemicellulose content ≤16.0wt%, lignin content ≤1.6wt%, and crystallinity index (CrI) ≥65%, and is suitable for subsequent bioconversion or material preparation.
[0027] Further, the above-mentioned saccharification product can be widely applied in the preparation process of bio-based materials, for example, can be used as a raw material of nanocellulose, and can be used as a substrate for bioethanol fermentation, and the ethanol yield in the conversion process can reach more than 90% of the theoretical value, and has good industrial popularization prospect.
[0028] Based on the above technical scheme, the corn straw ethanol amine pretreatment saccharification method of the application significantly improves the lignin removal rate and saccharification efficiency under mild conditions by optimizing the raw material treatment method and the reaction system. Specifically, by crushing the corn straw to a suitable particle size, mixing it with a certain volume fraction of ethanol amine aqueous solution, and reacting under controlled temperature and time conditions, and then through water washing and neutralization and constant temperature drying treatment, a saccharification product with high crystallinity and excellent component purity can be obtained.
[0029] The method not only realizes efficient removal of lignin in straw, with a lignin removal rate of 93.33±2%, but also the reducing sugar concentration in the obtained saccharification liquid is as high as 875.09±25mg / g dry straw, effectively improving the utilization efficiency of straw resources. In terms of lignin removal, the application first constructs and introduces a three-exponential superposition form of kinetic model, which can accurately describe the lignin degradation process in each stage, providing a theoretical basis for related biomass treatment processes.
[0030] In addition, the volume fraction, mixing ratio, reaction temperature and time parameters of the ethanol amine aqueous solution are systematically optimized, and the best process range is determined, so that the reaction conditions are more adaptable and controllable. The treated product not only has the advantages of high cellulose content, low hemicellulose and lignin content, but also has a crystallinity index (CrI) of not less than 65%, meeting the requirements of bio-based material preparation and subsequent fermentation utilization.
[0031] The application significantly improves the lignin removal rate and saccharification efficiency under mild reaction conditions by adjusting the parameters of ethanol amine aqueous solution. Compared with the prior art, it has the advantages of low equipment requirement, environmental friendliness and high conversion rate. The three-exponential kinetic model is first introduced to fit the lignin degradation process, which can accurately reflect the dynamic changes of the reaction and has strong theoretical and engineering value.
[0032] The saccharification product prepared by the application can be directly applied to the bioethanol fermentation process, and the ethanol conversion rate can reach more than 90% of the theoretical value, which is significantly higher than that of the raw material obtained by the traditional treatment method; it can also be used as a raw material for high-value-added materials such as nanocellulose, which helps to build a green, low-carbon and sustainable high-value utilization path for straw resources.
[0033] Therefore, the method of the present invention not only has simple process steps, controllable conditions, and moderate energy consumption, but also has cheap and easily available raw materials and excellent product quality, is suitable for large-scale industrial applications, and is of great significance to promoting the resource utilization of agricultural waste and the development of renewable energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 : Contour plot of hemicellulose content versus volume fraction and temperature;
[0035] Figure 2 : Three-dimensional response surface diagram of volume fraction and temperature on hemicellulose content;
[0036] Figure 3 : Contour plot of volume fraction versus time versus hemicellulose content;
[0037] Figure 4 : Three-dimensional response surface diagram of volume fraction and time to hemicellulose content;
[0038] Figure 5 : Contour plot of temperature and time on hemicellulose content;
[0039] Figure 6 : Three-dimensional response surface diagram of temperature and time on hemicellulose content;
[0040] Figure 7 : Contour plot of volume fraction and temperature versus cellulose content;
[0041] Figure 8 : Three-dimensional response surface diagram of volume fraction and temperature to cellulose content;
[0042] Figure 9 : Contour plot of volume fraction and time versus cellulose content;
[0043] Figure 10 : Three-dimensional response surface diagram of volume fraction and time to cellulose content;
[0044] Figure 11 : Contour plot of temperature and time on cellulose content;
[0045] Figure 12 : Three-dimensional response surface diagram of temperature and time on cellulose content;
[0046] Figure 13 : Contour plot of volume fraction and temperature versus lignin content;
[0047] Figure 14 : Three-dimensional response surface diagram of volume fraction and temperature to lignin content;
[0048] Figure 15 : Contour plot of volume fraction and time versus lignin content;
[0049] Figure 16 : Three-dimensional response surface diagram of volume fraction and time to lignin content;
[0050] Figure 17 : Contour plot of temperature and time on lignin content;
[0051] Figure 18 : Three-dimensional response surface diagram of temperature and time on lignin content;
[0052] Figure 19 : Graph showing the change curve of the residual amount of lignin and the equation fitting curve; in the figure, WL represents the residual amount of lignin (%), t represents the treatment time (h), and the curve is the result of three-exponential fitting. DETAILED DESCRIPTION
[0053] The corn straw ethanolamine pretreatment saccharification method of the present invention will be further described below with reference to specific experimental data, but the present invention is not limited to the following examples.
[0054] Example 1: Effect of different volume fractions of ethanolamine aqueous solution on saccharification of corn straw In order to explore the effect of the volume fraction of ethanolamine aqueous solution on the pretreatment of corn straw and the composition of saccharification products, the following experiment was designed.
[0055] Weigh 10.0 g of corn straw sample, crush it using a high-speed grinder, and sieve it to obtain a uniform sample with a particle size range of 20–60 mesh. Place the crushed sample in a 250 mL conical flask.
[0056] Prepare 10%, 20%, 30%, 40%, 50% and 60% ethanolamine aqueous solutions in sequence, add 200 mL of solution to each bottle respectively, keep the material-liquid ratio at 1:20 g / mL, and ensure sufficient liquid-solid contact.
[0057] Place the reaction flask in a constant temperature water bath shaker and continue the reaction at 30°C and 180 rpm for 3 hours. After the reaction is completed, quickly separate the solid and liquid by filtration, and repeatedly wash the residue with distilled water until the pH of the filtrate is close to neutral to remove free ethanolamine.
[0058] The washed residue was placed in a forced air drying oven at 105°C and dried to constant weight. Each sample was processed three times and the average value was taken for analysis.
[0059] The dried solid saccharification product is used for subsequent component analysis, including:
[0060] Determination of cellulose, hemicellulose, and lignin content (according to the national standard NREL method or Van Soest method);
[0061] Calculation of lignin removal rate:
[0062]
[0063] Among them, m0 and C0 are the original mass and its lignin mass fraction, respectively, and m1 and C1 are the mass and lignin mass fraction of the treated residue, respectively.
[0064] In addition, the reducing sugar content was determined to evaluate the initial saccharification efficiency, and the 3,5-dinitrosalicylic acid (DNS) method was used for colorimetric quantification at a wavelength of 540 nm.
[0065] Observation results:
[0066] As the ethanolamine volume fraction increased, the lignin content in the treated residue gradually decreased, while cellulose became relatively enriched. The 40% volume fraction treatment group exhibited the optimal balance between lignin removal efficiency and reducing sugar yield. The 10% and 20% treatment groups showed weaker lignin removal, while the 60% treatment group, while having a high removal efficiency, exhibited relatively poor economic and operational safety.
[0067] Example 2:
[0068] Under the condition that the volume fraction of ethanolamine aqueous solution is preferably 40%, in order to further investigate the effect of reaction temperature on the pretreatment effect of corn straw, treatment experiments were carried out under different temperature conditions.
[0069] Specifically, 10.0 g of corn straw, crushed to a mesh size of 20–60, was weighed and added to 200 mL of a 40% aqueous ethanolamine solution (solid-to-liquid ratio of 1:20 g / mL). Mixed thoroughly, the mixture was placed in a 250 mL conical flask. The samples were then placed in a thermostatic water bath shaker at 30°C, 40°C, 50°C, 60°C, 70°C, and 80°C. The reaction time was set to 3 hours, and the shaking speed was controlled at 180 rpm.
[0070] After the reaction is complete, the residue is immediately filtered to separate the filtrate. The residue is then washed several times with distilled water until the pH of the filtrate is close to neutral. The resulting neutral residue sample is air-dried at 105°C to a constant weight and analyzed as a saccharification product.
[0071] The dried saccharification products were measured for cellulose, hemicellulose, and lignin content using national standards or commonly used methods from the literature (such as the NREL method or the Van Soest method). The lignin removal rate was calculated by comparing the lignin content and residue mass before and after treatment. To evaluate saccharification efficiency, the reducing sugar concentration in the saccharification solution was further determined using the DNS colorimetric method to reflect the effect of treatment temperature on cellulose conversion. X-ray diffraction (XRD) was also used to measure the crystallinity index (CrI) of the products from each temperature treatment group to analyze the changes in cellulose structure.
[0072] Experimental results show that increasing the treatment temperature gradually improves the lignin removal rate, significantly increases the reducing sugar yield, and enriches the cellulose content. At 70°C, the cellulose mass fraction in the saccharification product reaches 74.5%, while the residual lignin content drops to 1.58%. This corresponds to a lignin removal rate of 93.33%, a reducing sugar yield of 875.09 mg / g dry straw, and a crystallinity index exceeding 65%. Further increases to 80°C yielded slight improvements in these indicators, but the magnitude was small and did not demonstrate a significant advantage.
[0073] Comprehensive analysis shows that temperatures between 30°C and 70°C significantly promote corn straw structural decomposition and component conversion, while temperatures above 70°C tend to plateau. Therefore, this example demonstrates that temperature, as a key reaction parameter, plays an important regulatory role in the pretreatment system of the present invention and clearly identifies 70°C as the optimal temperature for ethanolamine pretreatment of corn straw.
[0074] Example 3:
[0075] In order to further clarify the effect of reaction time on the ethanolamine pretreatment effect of corn straw, comparative experiments were carried out with different reaction times set at a fixed volume fraction of 40% ethanolamine aqueous solution and a treatment temperature of 60°C.
[0076] Specifically, 10.0 g of corn stover, crushed to a mesh size of 20–60, was weighed and added to 200 mL of a 40% aqueous ethanolamine solution (solid-to-liquid ratio of 1:20 g / mL). After thorough mixing, the mixture was placed in a 250 mL conical flask. The samples were then placed in a 60°C water bath for different reaction times: 4, 6, 8, 10, 12, and 16 hours, with an oscillation speed of 180 rpm to ensure uniform heating and sufficient reaction.
[0077] After the reaction, solid-liquid separation, water washing and neutralization, and forced air drying at 105°C were performed in the same order as described above. The resulting dried samples were analyzed for component content, including the determination of the mass fractions of cellulose, hemicellulose, and lignin, and the evaluation of reducing sugar yield.
[0078] The experimental results showed that as treatment time increased, the lignin content in the samples continued to decrease, while the sugar yield gradually increased. At 4 hours of treatment, only some lignin depolymerized, leaving a high residual lignin content and limited exposure to cellulose. The 6- and 8-hour treatment groups showed a clear trend of lignin degradation, with significantly enhanced saccharification. By 10 hours of treatment, lignin removal had significantly increased, and sugar yields approached saturation. Further treatments of 12 and 16 hours showed a slowing of lignin content changes, while sugar yields remained largely stable, indicating that the system reached equilibrium between 10 and 12 hours.
[0079] Specifically, after 10 hours of treatment, the residual lignin in the saccharification product was reduced to 1.64%, corresponding to a lignin removal rate of 91.2%, and a reducing sugar concentration exceeding 820 mg / g dry straw. After extending the treatment to 12 hours, the lignin content was further reduced to 1.59%, and the reducing sugar yield increased to 860 mg / g dry straw. However, after 16 hours, there was little change, with an increase of less than 2%. This shows that excessively long treatment times have limited effect on improving product quality and may even lead to unnecessary energy consumption and increased costs.
[0080] The results of this example show that at a reaction temperature of 60°C and a concentration of 40% ethanolamine, the treatment time has a significant effect on lignin removal and saccharification efficiency. The recommended reaction time is preferably controlled in the range of 10–12 hours, which can improve process economy and practical application efficiency while ensuring product quality.
[0081] Example 4:
[0082] Based on the process optimization results obtained in the aforementioned experiments, the optimal reaction parameters for the corn straw saccharification pretreatment of the present invention were determined to be a combination of a 40% volume fraction of an ethanolamine aqueous solution, a treatment temperature of 70°C, and a reaction time of 12 hours. To verify the stability and practicality of this process under scale-up conditions, a large-scale sample processing experiment was conducted in this example.
[0083] In the implementation process, 100g of dried corn straw was pulverized using a high-efficiency grinder and sieved to a particle size range of 20–60 mesh to ensure uniform sample size. The pulverized straw was then thoroughly mixed with 2000mL of a 40% (volume fraction) aqueous ethanolamine solution, maintaining a solid-liquid ratio of 1:20g / mL. The mixture was transferred to a 5L stainless steel reactor and reacted continuously at 70°C for 12 hours under a constant temperature control system, while maintaining slow mechanical stirring to enhance liquid-solid contact and mass transfer efficiency.
[0084] After the reaction is complete, hot filtration is immediately performed to quickly separate the liquid and solid phases to prevent secondary reactions or thermal degradation. The separated solid residue is washed several times with distilled water until the pH of the filtrate approaches neutral, ensuring complete removal of residual ethanolamine. The neutral residue sample is dried in a forced air drying oven at 105°C for 6 hours until constant weight is achieved.
[0085] Samples of the resulting saccharification product were analyzed for composition. Using standard cellulose analysis methods, the product showed a cellulose mass fraction of 74.5%, a hemicellulose content of 15.7%, and a residual lignin content of 1.6%. X-ray diffraction analysis revealed a crystallinity index (CrI) exceeding 65%. Furthermore, reducing sugar content was measured in the pretreatment solution after enzymatic hydrolysis or chemical saccharification. The results showed a reducing sugar yield of 875.09 ± 25 mg / g dry straw, and a lignin removal rate of 93.33 ± 2%.
[0086] These results fully demonstrate the excellent stability of saccharification and product quality under the process conditions of this invention. Furthermore, efficient lignin removal and sugar yield are maintained even when the feedstock processing rate is scaled up to 100 grams. This experiment provides a feasible basis for subsequent industrial scale-up to kilogram and ton levels, and also demonstrates the promising industrial application prospects and process scalability of this method.
[0087] Example 5: Lignin removal kinetics modeling and parameter fitting
[0088] In order to explore the removal rules of lignin in corn straw during ethanolamine pretreatment and establish a scientific and reasonable kinetic model to characterize its reaction process, this embodiment conducts a time-sharing sampling experiment under the optimal process conditions (ethanolamine aqueous solution volume fraction of 40% and reaction temperature of 70°C), and performs fitting analysis on the obtained data.
[0089] The experimental method is as follows:
[0090] Weigh 10.0 g of ground corn straw sample, sieved through a 20–60 mesh screen, add 200 mL of a 40% aqueous ethanolamine solution (solid-to-liquid ratio of 1:20 g / mL), and place in a 70°C constant-temperature water bath shaker to react. Set the reaction times to 3, 4, 6, 8, 10, and 12 hours. After the reaction is complete, terminate the reaction immediately. The procedure is as follows:
[0091] Separate the solid and liquid by suction filtration;
[0092] Wash the residue with distilled water until the pH of the filtrate is about 7;
[0093] Air-dried at 105°C to constant weight;
[0094] The lignin content was determined and its residual rate was calculated.
[0095] The measured results are as follows:
[0096]
[0097] The data showed that lignin degraded rapidly mainly in the first 8–10 hours, then stabilized and the reaction gradually reached a plateau.
[0098] Kinetic model construction:
[0099] The lignin removal process can be divided into the following three stages:
[0100] Main reaction stage: mainly involves β-O-4 and other structures that are easy to break;
[0101] Medium-speed reaction stage: mainly characterized by the breakage of relatively stable bonds;
[0102] Slow reaction stage: the slow degradation of inert structures in the remaining lignin.
[0103] Considering that the initial sampling time point is 3 hours, the initial rapid lignin removal stage has been basically completed, so the kinetic model can adopt the following three-exponential superposition form:
[0104] W L =a1exp(-k1t)+a2exp(-k2t)+a3exp(-k3t)
[0105] in:
[0106] W L represents the residual mass fraction (%) of lignin at treatment time t (unit: h);
[0107] a1, a2, and a3 are the corresponding lignin component ratios of each stage, satisfying a1+a2+a3=1, and the sum of the lignin component ratios of the three stages is 1;
[0108] K1, k2, and k3 are the reaction rate constants of each stage, which are obtained by fitting the experimental data.
[0109] The fitting results are:
[0110] W L =0.9642·exp(-k1t)+0.0180·exp(-0.0776t)+0.0178·exp(
[0111] -0.0774t)
[0112] Where a1 = 0.9642, a2 = 0.0180, a3 = 0.0178, and rate constant k2 = 0.0776 h -1 , k3=0.0774h -1K1 is the rate constant of the main rapid reaction stage. Because its reaction rate is much higher than that of the latter two stages, it can be considered to be completed very quickly during modeling.
[0113] The fitted curve is highly consistent with the measured values, especially within 3–10 hours. Figure 19 As shown in the figure, the model can accurately reflect the dynamic characteristics of the lignin removal process and has good theoretical explanatory power and engineering predictability.
[0114] Since the initial data of the reaction were not included in the sampling range, the lignin removal in the stage corresponding to k1 was almost complete, so the near-instantaneous completion assumption was adopted in the modeling. The specific proportional contribution was reflected in the a1 term, so the three-exponential superposition form used in the entire kinetic model can be further optimized as follows:
[0115] W L =0.9642·exp(-∞t)+0.0180·exp(-0.0776t)+0.0178·exp(-0.0774t).
[0116] Example 6: Response surface optimization design
[0117] To further optimize the process conditions for ethanolamine treatment of corn straw and systematically investigate the effects of ethanolamine volume fraction, treatment temperature, and treatment time on the composition of saccharification products, this example used the Box-Behnken design (BBD) in the response surface methodology (RSM) to optimize the treatment process.
[0118] (1) Experimental variables and level settings
[0119] The volume fraction of ethanolamine (X1), treatment temperature (X2) and treatment time (X3) were selected as three-factor variables, and the experimental combinations were set at three levels for each factor. The variables and their levels are shown in Table 1.
[0120] Table 1 Process variables, code values and variation intervals of the BBD experimental design for ethanolamine-treated corn straw
[0121] factor variable Level -1 Level 0 Level +1 <![CDATA[X1]]> Ethanolamine volume fraction (%) 20 40 60 <![CDATA[X2]]> Temperature (℃) 50 70 90 <![CDATA[X3]]> Time (h) 6 10 14
[0122] A total of 17 experimental combinations were set up according to the Box-Behnken principle. The specific experimental design and response value results are shown in Table 2. In each experiment, the hemicellulose, cellulose, and lignin contents of the treated corn straw were measured, and the average values were used as the response variables to enter the model.
[0123] Table 2 Experimental design of BBD of corn straw treated with ethanolamine and corresponding response variable values
[0124]
[0125]
[0126] (2) Response model construction and regression analysis
[0127] The experimental results were regressed and modeled using Design-Expert software, constructing quadratic polynomial models between hemicellulose content (Y1), cellulose content (Y2), and lignin content (Y3) and the three factors. The resulting mathematical model is as follows:
[0128] Hemicellulose content model:
[0129] Y1=18.10-3.34X1-1.15X2-1.03X3+1.06X1X2+0.84X1X3-0.14X2X3+2.73X1 2 +1.10X2 2 -0.85X3 2
[0130] Cellulose content model:
[0131] Y2=66.79+7.91X1+2.33X2+1.09X3+0.94X1X2-0.70X1X3-0.79X2X3-2.00X1 2 -3.33X2 2 +3.18X3 2
[0132] Lignin content model:
[0133] Y3=1.59-1.73X1-0.15X2-0.27X3+0.042X1X2+0.067X1X3+0.11X2X3+1.54X1 2 +0.49X2 2 -0.30X3 2
[0134] (3) Statistical analysis of regression parameters
[0135] Regression significance analysis was performed on each factor and its interaction term in the model. The main parameter estimates, errors, and confidence intervals are summarized in Table 3 (hemicellulose), Table 4 (cellulose), and Table 5 (lignin). The results showed that some linear terms and interaction terms reached significant or extremely significant levels, indicating that the model has good fit and predictive ability.
[0136] Table 3: Statistical parameters of hemicellulose content
[0137] Factor Estimate df Error Low High VIF Intercept 18.1 1 0.78 16.26 19.94 — A-volume fraction -3.34 1 0.61 -4.8 -1.89 1 B-Temperature -1.15 1 0.61 -2.6 0.3 1 C-Time -1.03 1 0.61 -2.48 0.42 1 AB 1.06 1 0.87 -1 3.11 1 AC 0.84 1 0.87 -1.21 2.9 1 BC -0.14 1 0.87 -2.2 1.91 1 A^2 2.73 1 0.85 0.73 4.74 1.01 B^2 1.1 1 0.85 -0.91 3.1 1.01 C^2 -0.85 1 0.85 -2.85 1.15 1.01
[0138] Table 4 Statistical parameters of cellulose content
[0139] Factor Estimate df Error Low High VIF Intercept 66.79 1 1.17 64.03 69.56 A-volume fraction 7.91 1 0.92 5.72 10.09 1 B-Temperature 2.33 1 0.92 0.15 4.51 1 C-Time 1.09 1 0.92 -1.09 3.27 1 AB 0.94 1 1.31 -2.15 4.03 1 AC -0.7 1 1.31 -3.79 2.39 1 BC -0.79 1 1.31 -3.88 2.29 1 A^2 -2 1 1.27 -5.01 1.01 1.01 B^2 -3.33 1 1.27 -6.34 -0.32 1.01 C^2 3.18 1 1.27 0.17 6.19 1.01
[0140] Table 5 Statistical parameters of cellulose content
[0141] Factor Estimate df Error Low High VIF Intercept 1.59 1 0.21 1.1 2.08 A-volume fraction -1.73 1 0.16 -2.12 -1.35 1 B-Temperature -0.15 1 0.16 -0.54 0.23 1 C-Time -0.27 1 0.16 -0.66 0.12 1 AB 0.042 1 0.23 -0.51 0.59 1 AC 0.067 1 0.23 -0.48 0.61 1 BC 0.11 1 0.23 -0.44 0.65 1 <![CDATA[A ^2 ]]> 1.54 1 0.23 1.01 2.08 1.01 B ^2 ]]> 0.49 1 0.23 -0.04 1.03 1.01 <![CDATA[C ^2 ]]> -0.3 1 0.23 -0.83 0.24 1.01
[0142] (IV) Response surface diagram and interaction analysis ( Figure 1 – Figure 18 )
[0143] In order to intuitively analyze the interaction relationship between the variables, a three-dimensional response surface diagram and a contour map were drawn based on the regression model, as shown in Figures 1 to 18 The main observations are as follows:
[0144] 1. Hemicellulose content
[0145] X1 (volume fraction) and X2 (temperature) interact significantly, and the contour lines are elliptical, such as Figure 1 、 Figure 2 As shown;
[0146] The interaction between X1 and X3 (time) is not significant, and the contour lines are arc-shaped, such as Figure 3 、 Figure 4 As shown;
[0147] X2 and X3 interact significantly, forming a saddle-shaped surface, such as Figure 5 、 Figure 6 shown.
[0148] 2. Cellulose content
[0149] X1 and X2 interact significantly, and the volume fraction has a greater impact, such as Figure 7 、 Figure 8 As shown;
[0150] X1 and X3 interact significantly, and the response surface is saddle-shaped, such as Figure 9 、 Figure 10 As shown;
[0151] The interaction between X2 and X3 is not significant, and the response surface changes slowly, such as Figure 11 、 Figure 12 shown.
[0152] 3. Lignin content
[0153] X1 and X2 interact significantly, and the temperature effect is more obvious, such as Figure 13 、 Figure 14 As shown;
[0154] The interaction between X1 and X3 is not significant, such as Figure 15 、 Figure 16 As shown;
[0155] The interaction between X2 and X3 is not significant, and the slope of the response surface is gentle, such as Figure 17 、 Figure 18 shown.
[0156] Based on the response surface analysis results, the optimal treatment conditions were determined to be: an ethanolamine volume fraction of 51.65%, a treatment temperature of 72.11°C, and a treatment time of 14 hours. Under these conditions, the residual lignin content of corn straw was minimal, at only 0.57%, while the hemicellulose content was 15.63% and the cellulose content was 74.63%. This validated the accuracy of the model predictions and the effectiveness of the response surface methodology in process optimization.
[0157] In summary, the present invention provides a corn straw ethanolamine pretreatment saccharification method with mild process conditions, high saccharification efficiency, and significant lignin removal effect. This method effectively destroys the lignin structure in the straw and improves the cellulose exposure and conversion rate by optimizing parameters such as ethanolamine concentration, reaction temperature, and time; and introduces a three-exponential superposition kinetic model to scientifically describe the lignin removal behavior, providing theoretical support for related process control. The resulting saccharification product has a high cellulose content and excellent crystallinity, is suitable for the preparation of a variety of bio-based materials and energy products, and has good industrial promotion prospects and ecological and environmental benefits. The method of the present invention is simple, green, and scalable, and has a wide range of application value.
[0158] It should be understood that the embodiments disclosed in this specification are intended only to illustrate the technical principles and effects of the present invention and do not constitute a limitation on the scope of protection of the present invention. Any technical solution obtained by using equivalent replacement methods or equivalent deformation methods based on the technical content disclosed by the present invention shall fall within the scope of protection of the present invention. The scope of protection of the present invention shall be based on the content defined in the claims.
Claims
1. A method for saccharifying corn stalks with ethanolamine, characterized in that: The following steps are involved: (a) crushing corn stalks into 20-60 mesh particles; (b) mixing the crushed corn stalks with a 10% to 60% by volume aqueous solution of ethanolamine at a ratio of 1:10 to 1:25 (g / ml); (c) reacting at a constant temperature of 30-80° C. for 3-16 hours; (d) washing the solid residue with water until it is neutral after solid-liquid separation, and drying to obtain a saccharification product; The method enables the reducing sugar content in the saccharification liquid to reach 875.09±25 mg / g dry straw, and the lignin removal rate is 93.33±2%.
2. The method according to claim 1, wherein: The volume fraction of the ethanolamine aqueous solution in step (b) is 40±5%, and the mixing ratio of corn straw to the solution is 1:20±2 (g / ml).
3. The method according to claim 1, wherein: The reaction conditions of step (c) satisfy any of the following parameters: (i) reacting at 60-80°C for 10±2 hours; or (ii) Incubate at 70±2°C for 8-12 hours.
4. The method according to claim 1, wherein: The drying condition of step (d) is to dry the mixture at 105±5° C. under forced air drying for 6±0.5 hours to a constant weight.
5. The method according to claim 1, wherein: The ethanolamine is selected from at least one of monoethanolamine, diethanolamine and triethanolamine, and the total molar concentration of ethanolamine in the solution is 1.5-6.0 mol / L.
6. The method according to claim 1, wherein: The lignin removal process conforms to the following three-exponential superposition kinetic model: W L =a1exp(-k1t)+a2exp(-k2t)+a3exp(-k3t) Among them, W L is the residual mass fraction (%) of lignin at reaction time t (unit: h), a1, a2, and a3 are the proportional coefficients of lignin at different stages, satisfying a1+a2+a3=1; K1, k2, and k3 are the lignin degradation rate constants corresponding to each stage; Preferably, K1 represents the rate constant of the rapid reaction stage (K1 = ∞), and its value is much larger than k2 and k3. The corresponding stage is completed rapidly at the beginning of the reaction and can be regarded as instantaneous removal in modeling and fitting; The parameters are obtained through regression fitting of experimental data and are used to describe the multi-stage degradation characteristics of lignin.
7. A corn straw saccharification product prepared by the method according to any one of claims 1 to 6, characterized in that: Cellulose content ≥74.5wt%; Hemicellulose content ≤16.0wt%; Lignin content ≤1.6wt%; Crystallinity index (CrI) ≥ 65%.
8. A use of the saccharification product according to claim 7 in the preparation of bio-based materials, characterized in that include: As raw material for nanocellulose preparation; or As a substrate for bioethanol fermentation, the ethanol conversion rate is ≥90% of the theoretical value.